Permainan Edukatif Kotak Barang sebagai Alternatif Peningaktan Penguasaan Mufrodat Siswa - Anisatin Islamiyah; Rosikh, Fahrur; Rohman, M. Fathor (Edu Journal Innovation in Learning and Education, 2024)
The process of learning Arabic is still considered difficult by students, lazy, not to mention students who from the beginning have considered Arabic difficult, they will automatically feel burdened to learn Arabic and not so responsive during the teaching and learning process. In addition, the lack of mastery of vocabulary makes it difficult for students to learn and master Arabic. This study examines the educational game of the goods box as an alternative in learning Arabic, especially vocabulary. This study uses a quantitative approach with an experimental research method. The results of this study are: the application of the educational game of the goods box which was carried out in five meetings, was considered very helpful in fostering the spirit of learning and improving vocabulary and the quality of students' understanding so that students become more active in class. And there is a significant influence of the application of the goods box game on improving mastery of vocabulary in class VII students of SMP Ma'arif Sumurber Panceng Gresik. This is evidenced by the pre-test score with a total of 435, an average score of 43.5. And the post-test score was 885, an average score of 88.5. So it is proven by the increase in value of 450. The box game also has a significant influence, this is proven by the results of the t-count analysis which is higher than the t-table at a significant level of 0.05 in the T-distribution table, namely 19.100> 2.262. And also at a significant level of 0.01, namely 19.100> 1.833.